2022
DOI: 10.3390/atmos13111788
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated System Dynamics Model and Life Cycle Assessment for Cement Production in South Africa

Abstract: Cement is one of the most produced materials globally. Population growth and urbanization cause an increased demand for the cement needed for expanding infrastructures. As a result of this circumstance, the cement industry must find the optimum compromise between increasing cement production and reducing the negative environmental impact of that production. Since cement production uses a lot of energy, resources and raw materials, it is essential to assess its environmental impact and determine methods for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…The cement industry has used a variety of alternative fuels around the world, including waste from wastewater treatment plants, industrial wastes (such as plastic waste and scrap tires) [51,52], wood residue [53][54][55], and biomass waste [56][57][58][59]. Moreover, innovative materials in cement production, such as blended Portland cement, might also be significant in producing sustainable cement [42,60]. Several studies have investigated the environmental impacts of cement production in the United States [29,61], Europe [48,[62][63][64][65], India [66], Africa [67][68][69][70], Canada [71], Japan [72][73][74], Hong Kong [54], and China [75][76][77][78][79].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The cement industry has used a variety of alternative fuels around the world, including waste from wastewater treatment plants, industrial wastes (such as plastic waste and scrap tires) [51,52], wood residue [53][54][55], and biomass waste [56][57][58][59]. Moreover, innovative materials in cement production, such as blended Portland cement, might also be significant in producing sustainable cement [42,60]. Several studies have investigated the environmental impacts of cement production in the United States [29,61], Europe [48,[62][63][64][65], India [66], Africa [67][68][69][70], Canada [71], Japan [72][73][74], Hong Kong [54], and China [75][76][77][78][79].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some cement plants in the country use only low-grade limestone as a raw material for clinker production [40]. Portland Cement (CEM I) is the most commonly produced cement product in South Africa, followed by blended cement products such as CEM II-CEM III, with 16 integrated cement plants within the country [41,42] using the dry process [18,43,44]. CEM I cement is Portland cement with more than 95% clinker content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oluwafemi constructed an SD model for the cement production industry carbon emissions trend in South Africa and predicted that the carbon emissions of cement production in South Africa will double by 2040. 9 11 Onat used SD to study the impact of US green building-related policies on carbon emission trends and concluded that building renovation policies could improve carbon emission trends better than new net-zero buildings or high-performance green buildings. 12 Li et al constructed a SD model of Hebei Province including seven subsystems, such as population, economy, secondary industry, and policy.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have adopted the SD method to research carbon emissions in countries or regions. Oluwafemi constructed an SD model for the cement production industry carbon emissions trend in South Africa and predicted that the carbon emissions of cement production in South Africa will double by 2040 9 . Mirzaei et al established an SD model of Iran's carbon emission trend from 2000 to 2025 and set up three scenarios considering energy policy factors to analyze Iran's carbon emissions under different energy intensity reduction scenarios 10 .…”
Section: Introductionmentioning
confidence: 99%